Lacking P2X7-receptors protects substantia nigra dopaminergic neurons and hippocampal-related cognitive performance from the deleterious effects of high-fat diet exposure in adult male mice - Rossi, Chiara; Distaso, Mariarosaria; Raggi, Francesco; Kusmic, Claudia; Faita, Francesco; Solini, Anna (Frontiers in Nutrition, 2024)
Background Dietary fat consumption, involved in the pathogenesis of insulin resistance and impaired glucose metabolism, is linked with decline in cognitive functions, dementia, and development of Parkinson’s disease and Alzheimer’s disease. Mature IL-1β, requiring the activation of the P2X7 receptor (P2X7R)-inflammasome complex, is an important mediator of neuroinflammation. The aim of the study was to test whether P2X7R activation might interfere with systemic and cerebral metabolic homeostasis. Methods We treated WT and P2X7R KO mice with a high-fat diet (HFD) for 16 weeks, evaluating the effects on the Substantia Nigra and Hippocampus, target areas of damage in several forms of cognitive impairment. Results HFD-treated WT and P2X7R KO mice showed a different brain mRNA profile of Insulin and Igf-1, with these genes and relative receptors, more expressed in KO mice. Unlike P2X7R KO mice, WT mice treated with HFD displayed a diameter reduction in dopaminergic neurons in the Substantia Nigra, accompanied by an increased IBA1 expression in this area; they also showed poor performances during Y-Maze and Morris Water Maze, tasks involving Hippocampus activity. Conversely, Parkin, whose reduction might promote neuronal cell death, was increased in the brain of P2X7R KO animals. Conclusion We report for the first time that HFD induces damage in dopaminergic neurons of the Substantia Nigra and a Hippocampus-related worse cognitive performance, both attenuated in the absence of P2X7R. The involved mechanisms might differ in the two brain areas, with a predominant role of inflammation in the Substantia Nigra and a metabolic derangement in the Hippocampus.